2020
DOI: 10.31676/0235-2591-2020-3-5-10
|View full text |Cite
|
Sign up to set email alerts
|

A model of a commercial strawberry variety for the conditions of central Russia

Abstract: The article presents a model of a commercial variety of strawberry for the conditions of central Russia. This model covers 40 features and properties, which are combined into three groups: 1) plant resistance to a complex of adverse abiotic and biotic factors (adaptive potential); 2) productivity and quality of products; 3) manufacturability of the variety. In the middle zone of Russia, adapted strawberry varieties should develop normally and produce a high quality crop of 20-25 t/ha with the sum of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In this regard, F&VRI has obtained a unique collection of rootstocks and varieties from various fruit growing regions of the world, as well as varieties of local selection, which has replenished the agro-diversity of fruit crops in Kazakhstan. Long-term studies have identified a group of rootstocks with positive economic and biological characteristics, in particular, good adaptability to local soil and climatic conditions of growth, contributing to high productivity of trees with good fruit quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, F&VRI has obtained a unique collection of rootstocks and varieties from various fruit growing regions of the world, as well as varieties of local selection, which has replenished the agro-diversity of fruit crops in Kazakhstan. Long-term studies have identified a group of rootstocks with positive economic and biological characteristics, in particular, good adaptability to local soil and climatic conditions of growth, contributing to high productivity of trees with good fruit quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…В Российской Федерации по каждой плодовой и ягодной культуре разработаны, постоянно дополняются и уточняются параметры по накоплению важнейших питательных и биологически активных веществ. В плодах земляники современных промышленных сортов желательно содержание биологически активных веществ на следующем уровне: аскорбиновая кислотаболее 80 мг/100 г; антоцианы -более 80 мг/100 г (Kulikov et al, 2020). Проведенный нами корреляционный анализ между содержанием аскорбиновой кислоты и антоцианов показал отсутствие связи между данными показателями: коэффициент корреляции (r) составил -0,18 (Zhbanova et al, 2019).…”
Section: Introductionunclassified
“…Common garden strawberry is loved by the population for its unique taste and aroma, which explains its demand [3,4]. The composition of its berries includes easily digestible sugars, organic acids, ascorbic acid, phenolic (P-active) compounds, etc., which have an undeniably beneficial effect on the human body, have high physiological activity [5][6][7][8][9][10] and are part of the Mediterranean diet [11]. The consumption of strawberries significantly improves the overall antioxidant status of human blood [1].…”
Section: Introductionmentioning
confidence: 99%